Microencapsulation of fish oil using supercritical antisolvent process - Karim, Fahim Tamzeedul; Gahfoor, Kashif; Ferdosh, Sahena; Al-Juhaimi, Fahad; Ali, Eaqub; Yunus, Kamaruzzaman; Hamed, Mir Hoseini; Islam, Ashraful; Asif, Mohammad; Sarker, Md. Zaidul Islam (Elsevier Taiwan LLC, 2017)
In order to improve the encapsulation process, a newly supercritical antisolvent process was developed to encapsulate fish oil using hydroxypropyl methyl cellulose as a polymer. Three factors, namely, temperature, pressure, and feed emulsion rate were optimized using response surface methodology. The suitability of the model for predicting the optimum response value was evaluated at the conditions of temperature at 60C, pressure at 150 bar, and feed rate at 1.36 mL/min. At the optimum conditions, particle size of 58.35 mm was obtained. The surface morphology of the micronized fish oil was also evaluated using field emission scanning electron microscopy where it showed that particles formed spherical structures with no internal voids. Moreover, in vitro release of oil showed that there are significant differences of release percentage of oil between the formulations and the results proved that there was a significant decrease in the in vitro release of oil from the powder when the polymer concentration was high.